Effects of in Situ Firecrackers Explosion on Copepods (Crustacea, Copepoda) and Siganusguttatus (Pisces, Siganidae) Larvae - Metillo, Ephrime B.; Boco, Sheldon Rey E.; Malugao, Mac Euan D. (Asian Journal of Biological and Life Sciences, 2016)
Underwater explosives are used in illegal fishing,military operations, harbor construction and seismic exploration for oil and gas. However, very little is known about the impact of underwater explosions on fish larvae and zooplankton. An in situ experiment was conducted to assess the effects of low intensity sound from firecrackers on copepod zooplankton and 20-day old rabbitfish (Siganusguttatus) larvae. Either rabbitfish larvae or copepods were ensonified with separate low, medium, and high explosions of firecrackers detonated inside a blast container placed in the middle of a0.125 m3experimental cage with ambient seawater. Sound was recorded using a shockproof underwater video camera, and the recorded sound was converted into sound pressure levels indecibels (dB) and Pascals (Pa) using the Goldwave software. Mortality of copepods was determined using neutral red vital stain. No direct mortality effect was observed among fish larvae immediately after a blast, but across the three blast treatments 75-100% of larvae showed abnormal swimming behavior,abdominal distension, and bladder and intestinal injuries. Mortality of copepods increased with increasing level of explosion, and values reached up to 90%. The level of sound intensity in this study is several orders of magnitude lower than that at the core area of an average blast fishing explosion, but our results may reflect impact at the periphery of dynamited areas where reduced sound intensities may still cause high mortalities on copepods and fish larvae and very likely other zooplankton taxa.
Keywords: Copepoda; Explosives; Fish larvae; Siganusguttatus; Sound; Zooplankton